Influence of Mesostructure on Mechanical Property of Laminated Ti–Al Composites1 . Issue 8 (29th May 2017) - Lyu, Shaoyuan; Sun, Yanbo; Ren, Lei; Xiao, Wenlong; Ma, Chaoli
Abstract : Laminated Ti–Al composite sheets with different mesostructures have been fabricated through hot pressing. The influence of mesostructure on mechanical properties of the composite is investigated. The results indicate that with the increase of sintering temperature, different mesostructures of composite are obtained, that is, laminated Ti/Ti–Al composite, laminated Ti3 Al/TiAl composite, and monolithic Ti3 Al/TiAl composite. The mechanical properties tests reveal that laminated Ti/Ti–Al composite exhibits better comprehensive mechanical properties, including flexural strength, fracture toughness, and microhardness, than those of laminated Ti3 Al/TiAl composite and monolithic Ti3 Al/TiAl composite. The fracture analysis shows that the propagation route of crack is zigzag for Ti/Ti–Al composite, curving for laminated Ti3 Al/TiAl composite, and approximately a straight line for monolithic Ti3 Al/TiAl composite. The relevant strengthening and toughening mechanism of the composites is discussed. Abstract : Incorporating one ductile layer into the brittle Ti–Al composite is a potential way to overcome low ductility and fracture toughness at room temperature. By controlling the mesostructures of the composite, three types of composites are obtained, among which, laminated Ti/Ti–Al composite exhibits better comprehensive mechanical properties than those of laminated Ti–Al composite and monolithic Ti–Al composite.